The Enormity of Chronic Kidney Disease in Nigeria: The Situation in a Teaching Hospital in South-East Nigeria - Ifeoma I. Ulasi; Chinwuba K. Ijoma (Journal of Tropical Medicine)
Background. The magnitude of the problem of chronic kidney disease (CKD) is enormous, and the prevalence keeps rising. To highlight the burden of CKD in developing countries, the authors looked at end-stage renal disease (ESRD) patients seen at the University of Nigeria Teaching Hospital (UNTH), Enugu, South-East Nigeria. Method. ESRD patients seen from 01/05/1990 to 31/12/2003 were recruited. Records from A&E Department, medical-out-patients, wards and dialysis unit were used. Results. A total of 1001 male versus 537 female patients were reviewed. About 593 male versus 315 female patients had haemodialysis. The mean age was 42.55±15.43 years and 86.5% were <60 years. Primary renal disease could not be determined in 51.6% while hypertension and glomerulonephritis accounted for −17.2% and 14.6%, respectively. Death from renal causes constituted 22.03% of medical deaths. Conclusion. The prognosis for CKD patients in Nigeria is abysmal. Only few patients had renal-replacement-therapy (RRT). The prohibitive cost precludes many patients. This underscores the need for preventive measures to reduce the impact of CKD in the society.